Caregiver sociodemographic factors associated with adherence to zinc treatment of childhood diarrhoea, Kirinyaga county, Kenya - Mwangi, Livingstone W.; Munyekenye, Godwil; Nderu, David (International Journal Of Community Medicine And Public Health, 2026)
Background: Zinc supplement is critical for managing childhood diarrhoea. However, adherence to zinc treatment remains low in low-resource settings. This study determined the association between zinc utilization for treatment of diarrhoea among children below five years old and caregivers’ sociodemographic factors in Kirinyaga County, central Kenya. Methods: A cross-sectional study was conducted from February to March 2025, involving 223 caregivers and 25 healthcare workers across four hospitals. Results: Only 20% (45/223) of children in this study received zinc treatment for the recommended period of 10–14 days. Low adherence to zinc treatment was associated with caregiver level of education and employment status (p<0.05). Lack of IMNCI training (96%; 24/25) among health workers was observed, despite most of them having access to the IMNCI guidelines. Conclusions: Findings of this study underscore the need to sensitize caregivers on the benefits of zinc supplements in management of childhood diarrhea. These efforts should be complemented with periodic health worker training on guidelines that support effective management of childhood diarrhea in Kirinyaga County, particularly the IMNCI protocol.